Proteinaceous exotoxins of shrimp-pathogenic isolates of Vibrio penaeicida and Vibrio nigripulchritudo - G Aguirre-Guzmán; Y Labreuche; D Ansquer; B Espiau; P Levy; F Ascencio; D Saulnier (Ciencias Marinas, 2003)
The pathogenicity of two V. penaeicida strains, AM101 and KH-1, with different geographic origin, and V. nigripulchritudo strain AM102, were investigated in juvenile blue shrimp species Litopenaeus stylirostris. Alive bacteria and protein fractions (PFs) obtained from cell-free supernatants (CFS) were used in experimental challenges. Strains AM102, AM101, and KH-1 produced respectively 60, 54 and 12% mortality at 96 h after infection using 104 cfu mL–1 of bacterial suspension. Exocellular toxin-like factors were evidenced in CFS from the New Caledonian strains (AM102 and AM101) but not in the Japanese strain (KH-1). At 48 h post injection of each CFS, mortality rates were respectively 96, 98 and 5% when these strains were cultivated at 20 ºC, whereas only 0, 16 and 5% mortality rates were observed when these strains were cultivated at 30ºC. Clear differences in pathogenicity between both V. penaeicida strains of distinct geographic origin (AM101 and KH-1) were thus emphasized. Protein fractions were obtained from CFS of all the strains tested in this study and cultivated at 20ºC, by ammonium sulfate precipitation. Whatever the used strain, significantly higher mortalities were produced with PFs obtained with 0–40% of ammonium sulfate saturation, in respect to those produced with PFs60 and PFs80. Shrimp injected with PFs40 from strains AM102, AM101 and KH-1, and at a 20-µg org–1 dose produced respectively 100, 90 and 60% mortality 46 h after the challenge. The strain AM101 showed a median lethal dose of approximately 5 µg protein org–1 (1–1.25 µg protein g–1 body weight) 59 h after injection. The PFs40 from New Caledonian strains were found sensitive to heating and proteinase K treatments, reinforcing thus the hypothesis of their proteinaceous nature. Surprisingly, PFs40 from each bacterial strain displayed similar protein bands by SDS-PAGE suggesting that the tested strains share a common exotoxic compound regardless their distinct geographic origin or species.